Pengaruh Stres Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai - Candra Pranata Manihuruk; Satria Tirtayasa (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to determine the effect of work discipline, work motivation and work environment on employee morale at the North Labuhanbatu Population and Civil Registration Service either partially or simultaneously. This study uses an associative approach, which is research conducted to determine the effect or relationship between the independent variable and the dependent variable. The population and sample in this study were all permanent employees at the North Labuhanbatu Civil Registration and Population Service, totaling 32 people. The data collection technique used in this study was a questionnaire, while the data analysis used multiple linear regression analysis. The results showed that partially job stress had no significant effect on morale. Partially work motivation has a significant effect on morale. Partially the work environment has no significant effect on morale. Simultaneously work stress, work motivation and work environment have a significant influence on employee morale at the North Labuhanbatu Population and Civil Registration Service.